Infection control practices in dental school: A patient perspective from Saudi Arabia - Mohammad Abdul Baseer; Ghousia Rahman; Mona Ali Yassin (Wolters Kluwer Medknow Publications, 2013)
Background: Routine use of gloves, masks and spectacles are important in infection control. Aim of this study was to assess the knowledge and attitudes of infection control measures among the patients attending clinics of Riyadh Colleges of Dentistry and Pharmacy (RCsDP) in Saudi Arabia. Material and Methods: It was a cross-sectional descriptive study of a convenient sample of dental patients attending dental clinics of RCsDP. A structured, close ended, self-administered questionnaire was distributed to 350 patients and a response rate of 86% was obtained. Questionnaireconsisted of series of queries related to knowledge and attitudes of patients towards infection control measures. Data analysis included frequency distribution tables, Mann-Whitney and Kruskal-Wallis tests. Level of significance was set at P < 0.05. Results: Final study sample included 301 patients (147 males and 154 females). Almost 99%, 93.7% and 82.7% of the patients agreed that dentist should wear gloves, face mask and spectacles while providing treatment. However, 60.1%, 30% of the patients said that HIV and hepatitis-B infections can spread in dental clinics. Half of the patients felt that they were likely to contract AIDS and 77.7% refused to attend clinics if they knew that AIDS and Hepatitis-B patients treated there. Only 25.2% said that autoclave is the best method of sterilization. A significantly higher knowledge of infection control was observed among the previous dental visitors compared to the first time visitors to the dental clinics ( P < 0.05). Conclusions: Patients revealed adequate knowledge towards the use of gloves, face mask and spectacles by dentist. However, their knowledge regarding the spread of Hepatitis-B, HIV infection and use of autoclave was poor. Previous visitor of dental clinics showed higher knowledge of infection control as compared to the first time visitors. Many patients expressed their negative attitudes towards dental care due to AIDS and Hepatitis-B concerns.